Early subtypes and progressions of progressive supranuclear palsy: a data-driven brain bank study - Ono, Daisuke; Sekiya, Hiroaki; Ghayal, Nikhil B.; Maier, Alexia R.; Roemer, Shanu F.; Uitti, Ryan J.; Litvan, Irene; Josephs, Keith A.; Wszolek, Zbigniew K.; Dickson, Dennis W. (Journal of neurology, 2025)
Background Progressive supranuclear palsy (PSP) is typically characterized by vertical supranuclear gaze palsy and early falls, referred to as Richardson’s syndrome (PSP-RS). Other presentations include postural instability (PSP-PI), Parkinsonism (PSP-P), speech/language disorder (PSP-SL), frontal presentation (PSP-F), ocular motor dysfunction (PSP-OM), and corticobasal syndrome (PSP-CBS). However, differences across the early presentations and their subsequent clinical courses remain to be elucidated. Objective This study aimed to characterize early PSP subtypes and their subsequent progressions using a large postmortem dataset. Methods An automated pipeline incorporating fine-tuned Chat Generative Pretrained Transformer (ChatGPT) was developed. The pipeline collected 195 clinical features with onset information from autopsy-confirmed PSP cases without significant neurodegenerative co-pathologies. Results A structured clinicopathologic dataset from 588 patients was analyzed. The results from unsupervised clustering were distilled into a decision tree model. The mutually exclusive algorithm identified seven subtypes: PSP-PF (postural and frontal dysfunction), PSP-RS, PSP-PI, PSP-P, PSP-SL, PSP-F, and PSP-OM, based on five clinical manifestations: frontal presentation, postural instability, ocular motor dysfunction, speech/language disorder, and Parkinsonism. PSP-PF showed rapid progression, the shortest median disease duration (six years), and high tau burden in cortical and subcortical regions. In PSP-F, frontal presentation preceded other symptoms by four years, with a nine-year disease duration—second longest after PSP-P (10 years). PSP-CBS was not identified as an independent subtype. Conclusions This data-driven study identified a novel, aggressive PSP phenotype characterized by early postural and frontal dysfunction. Early subtyping using the decision tree model would help clinicians estimate progression and facilitate early patient recruitment for clinical trials.